Adaptation of Methanogenic Inocula to Anaerobic Digestion of Maize Silage - Wojcieszak, Martyna; Pyzik, Adam; Poszytek, Krzysztof; Krawczyk, Pawel S.; Sobczak, Adam; Lipinski, Leszek; Roubinek, Otton; Palige, Jacek; Sklodowska, Aleksandra; Drewniak, Lukasz (Frontiers in Microbiology, 2017)
A well-balanced microbial consortium is crucial for efficient biogas production. In turn, one of a major factor that influence on the structure of anaerobic digestion (AD) consortium is a source of microorganisms which are used as an inoculum. This study evaluated the influence of inoculum sources (with various origin) on adaptation of a biogas community and the efficiency of the biomethanization of maize silage. As initial inocula for AD of maize silage the samples from: (i) an agricultural biogas plant (ABP) which utilizes maize silage as a main substrate, (ii) cattle slurry (CS), which contain elevated levels of lignocelluloses materials, and (iii) raw sewage sludge (RSS) with low content of plant origin materials were used. The adaptation of methanogenic consortia was monitored during a series of passages, and the functionality of the adapted consortia was verified through start-up operation of AD in two-stage reactors. During the first stages of the adaptation phase, methanogenic consortia occurred very slowly, and only after several passages did the microbial community adapts to allow production of biogas with high methane content. The ABP consortium revealed highest biogas production in the adaptation and in the start-up process. The biodiversity dynamics monitored during adaptation and start-up process showed that community profile changed in a similar direction in three studied consortia. Native communities were very distinct to each other, while at the end of the Phase II of the start-up process microbial diversity profile was similar in all consortia. All adopted bacterial communities were dominated by representatives of Porphyromonadaceae, Rikenellaceae, Ruminococcaceae, and Synergistaceae. A shift from low acetate-preferring acetoclastic Methanosaetaceae (ABP and RSS) and/or hydrogenotrophic Archaea, e.g., Methanomicrobiaceae (CS) prevailing in the inoculum samples to larger populations of high acetate-preferring acetoclastic Methanosarcinaceae was observed by the end of the experiment. As a result, three independent, functional communities that syntrophically produced methane from acetate (primarily) and H2/CO2, methanol and methylamines were adapted. This study provides new insights into the specific process by which different inocula sampled from typical methanogenic environments that are commonly used to initiate industrial installations gradually adapted to allow biogas production from maize silage.